Milk somatic cell count-derived traits as new indicators to monitor udder health in dairy buffaloes. Issue 1 (1st January 2021) - Costa, Angela; De Marchi, Massimo; Neglia, Gianluca; Campanile, Giuseppe; Penasa, Mauro
Abstract: Milk somatic cell count (SCC), an indicator of udder health and milk hygiene, has not been implemented either in milk payment systems or in the current selection index of Italian buffalo so far. As a matter of fact, there is room to improve udder health through genetic and management strategies in this species. Repeated milk SCC test-day (TD) records on the same animal are useful to derive novel phenotypes on lactation basis by using somatic cell score (SCS) and thus to disclose buffaloes with udder issues to be monitored. In this study, sources of variation of SCC-derived traits in buffalo milk were investigated and their effect on milk yield and composition traits was estimated. Mean SCS (SCS150 ), standard deviation of SCS (SCS_SD150 ) and severity (SEV150, ratio between the number of TD SCC >200, 000 cells/mL and total number of TD available in the first 150 DIM) in the first 150 days in milk were calculated using TD data of 45, 312 lactations from 35, 623 buffaloes. Sources of variation of such traits were investigated through a linear model. Both SCS150 and SEV150 increased with parity, whereas SCS_SD150 decreased ( p  < .001). Subsequently, the three traits were separately included in the model as explanatory variables to estimate their effect on milk yield and composition traits. Results showed that milk yield and lactose content were lower in animals with high and variable SCS in the first 150 days of lactation ( p  < .001). This study opens the debate on the development of an udder health index for the Italian buffalo. HIGHLIGHTS: So far, somatic cell count has not been considered in payment systems of buffalo milk in Italy. There is need to improve mastitis resistance and udder health in dairy buffaloes. Traits derived from test-day records can be used for management and breeding purposes in buffaloes.